Integration einer OSCE in das zahnmedizinische Physikum [Integration of an Objective Structured Clinical Examination (OSCE) into the Dental Preliminary Exams] - Ratzmann, Anja (GMS Zeitschrift für Medizinische Ausbildung, 2012)
[english] Introduction: In the pre-clinical phase of the study of dentistry at the University of Greifswald, the course “Early Patient Contact (EPC)” is conducted within the framework of Community Medicine/Dentistry. The course is based on three pillars: the patient visiting program, special problem-oriented seminars, and communication training for doctors. The essential goal consists of providing students with real patient contact right at the beginning of their study of dentistry, thus making the study of dentistry patient-based very early on. Students are trained in taking comprehensive anamneses and recording clinical findings.Methods: Within the framework of the dental preliminary exams, the course is evaluated using an OSCE on a standardized patient. Furthermore, the added value of an additional training unit (conducting anamnesis and clinical examination) in preparation for the OSCE was evaluated. The exam results of a group without training (control group) were compared with those of a group with training (intervention group).Results: The intervention group performed significantly better than the control on the following items: the total number of points achieved on the OSCE early patient contact, and in the most important points of the anamnesis and clinical examination. In addition, the intervention group tended to score higher in terms of the item “oral health status”.Conclusion: The present study showed a positive effect of an additional training unit on students’ performance in the OSCE. Taking the limitations of the study and the results of a literature review into account, we recommend conducting such training as preparation for the OSCE. [german] Einleitung: An der Universität Greifswald wird im vorklinischen Abschnitt des Studienganges der Zahnmedizin im Rahmen der Community Medicine/Dentistry der Kurs „Der Frühe Patientenkontakt (FPK)“ durchgeführt. Der Kurs basiert auf drei Prinzipien: dem Patientenbesuchsprogramm, speziellen problemorientierten Seminaren und dem ärztlichen Kommunikationstraining. Die wesentliche Zielstellung besteht darin, den Studierenden bereits zu Beginn des Zahnmedizinstudiums einen realen Patientenkontakt zu ermöglichen und somit das Studium frühzeitig patientennah zu gestalten. Die Studierenden trainieren das Erheben einer umfangreichen Anamnese sowie die klinische Befundung.Methode: Der Kurs wird im Rahmen des zahnmedizinischen Physikums anhand eines OSCE an einem standardisierten Patienten überprüft. Das OSCE bestand aus den drei Stationen: Anamnesegespräch, Zahnstatus und Mundhygienestatus.Ziel: Es wurde der Mehrwert eines zusätzlichen Trainings (Anamnesedurchführung und klinische Untersuchung) in Vorbereitung auf die OSCE- Prüfung untersucht. Dazu wurden die Prüfungsleistungen einer Gruppe ohne Training (Kontrollgruppe) und einer Gruppe mit Training (Interventionsgruppe) verglichen.Ergebnisse: Die Interventionsgruppe war in folgenden Items signifikant besser als die Kontrollgruppe: in der erreichten Gesamtpunktzahl für das OSCE- Früher Patientenkontakt, sowie in den wichtigsten Punkten der Anamnese und der klinischen Untersuchung. Tendenziell zeigte die Experimentalgruppe zusätzlich bezüglich des Items „Mundhygienestatus“ höhere Rangwerte.Schlussfolgerung: In der vorliegenden Untersuchung konnte der positiver Effekt eines zusätzlichen Trainings auf die Prüfungsleistung im OSCE gezeigt werden. Unter Berücksichtigung der Limitation der Studie und der Ergebnisse des Literaturstudiums empfiehlt sich aus unserer Sicht die Durchführung eines solchen Trainings zur Vorbereitung auf die OSCE- Prüfung.